DECONTAMINATION OF ESCHERICHIA COLI O157: H7 AND STAPHYLOCOCCUS AUREUS FROM FRESH-CUT PARSLEY WITH NATURAL PLANT HYDROSOLS - Tornuk, Fatih; Dertli, Enes (WILEY, 2015)
The inhibitory effects of sage, rosemary, oregano and thyme hydrosols were evaluated against Escherichia coli O157: H7 and Staphylococcus aureus inoculated on parsley at high and low concentrations. Following the pathogen inoculations, parsley samples were washed with the hydrosols and sterile tap water as a control for 0, 20, 40 and 60 min, and reductions on pathogen counts were determined. Sterile tap water was ineffective on all conditions tested. After 20 min of application, oregano and thyme hydrosols were able to significantly (P < 0.05) reduce E. coli O157: H7 counts on low inoculum level, while all hydrosols showed significant reductions (P < 0.05) on high inoculum levels at this period. Additional reductions on E. coli O157: H7 counts were observed with the increasing time. S. aureus was more sensitive to hydrosol treatments, and oregano hydrosol was able to completely eliminate S. aureus after 40 min. In conclusion, decontamination of foodborne pathogens from fresh- cut vegetables can be achieved by hydrosol treatments.
Keywords: 4 PATHOGENIC BACTERIA; ESSENTIAL OILS; SALMONELLA-TYPHIMURIUM; ANTIBACTERIAL ACTIVITY; EFFICACY; EXTRACTS; OREGANO; INACTIVATION; CONSTITUENTS; SANITIZERS; Food Science & Technology